Residue analysis of premix formulation of fipronil and imidacloprid and its metabolites in hot pepper (Capsicum annum) - REENA CHAUHAN; SUSHIL AHLAWAT; SURENDER SINGH YADAV; NISHA AHLAWAT; INDU CHOPRA (The Indian Journal of Agricultural Sciences)
A field experiment was conducted during 2018–19 and 2019–20 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to assess the dissipation pattern of a ready mix formulation i.e. fipronil and imidacloprid along with their metabolites in fruits of hot pepper (Capsicum annum L.). The Hot pepper variety Kranti was used for the study. Quantitative analysis was done on gas liquid chromatography (GLC) and high pressure liquid chromatography (HPLC) for fipronil and imidacloprid with their metabolites, respectively. At the suggested dose, fipronil residues were lower than 0.01 mg/kg in the studied years. However, in double doses, the total residues of fipronil were detected on the 5th (0.071 mg/kg) and 3rd (0.043 mg/kg) day for the 1st and 2nd year following drench application. Imidacloprid was detected only in the subsequent year’s trial in double doses. Residual leftovers of imidacloprid metabolite (6- CNA) were lower than 0.01 mg/kg (LOQ). No residual leftovers were present in fully ripened red chilli and harvest time samples of soil.